Iphigénie à Paris: Positioning Gluck Historically in Early Twentieth-Century France - Gibbons, William (Intersections)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2006)
In December 1907, Gluck's opera Iphigénie en Aulide was produced in Paris at the Opéra-Comique, the last of his major operas to be revived in France. The ensuing critical reception pitted Vincent d'Indy, who harshly criticized the production, against its director, Albert Carré; d'Indy further responded by conducting the overture to Iphigénie only a few weeks later as a musical corrective to the performance at the Opéra-Comique. This unusual event highlights the historiographie problem Gluck presented to early twentieth-century critics in France: did his music look backwards to the tragédies lyriques of Lully and Rameau, or did it prefigure the Wagnerian music-dramas of the nineteenth century? The 1907 Opéra-Comique production of Iphigénie and its aftermath encapsulate the struggle to incorporate Gluck into newly developing and often competing narratives of music history.